Stress and reactivity in three Italian chicken breeds. Issue 2 (2nd April 2016) - Ferrante, Valentina; Mugnai, Cecilia; Ferrari, Lorenzo; Marelli, Stefano P.; Spagnoli, Enrico; Lolli, Susanna
Abstract: Heterophil to lymphocyte ratio, plasma corticosterone and tonic immobility test, plumage and leg score (Food Pad Dermatitis, FPD) are frequently used as indicators of welfare in chickens. Three traditional Italian chicken breeds (60 birds/group) were studied: Valdarnese Bianca (VB), Bionda Piemontese (BP) and Robusta Maculata (RM). At 80 days of age, reactivity was tested through Tonic Immobility (TI) and plumage and leg score tests. Immediately after phenotypical and behavioural tests, the blood samples were collected from the ulnar vein of chickens. TI duration was not significant among the breeds (VB 72.2 ± 8.3 s; BP 95.2 ± 9.0 s; RM 76.5 ± 8.6 s; mean ± SEM). RM and BP needed a mean number of induction significantly higher than VB (RM = 1.84 ± 0.1; BP = 1.96 ± 0.1; VB = 1.38 ± 0.1; p  < 0.0001). The highest corticosterone mean concentration (3.4 ± 0.23 ng/mL) was found in the VB breed, whereas the lowest (1.71 ± 0.21 ng/mL) was found in BP birds. The heterophil to lymphocyte (H/L) ratio was significantly ( p  < 0.0001) higher in the VB breed (0.86 ± 0.03) than BP (0.78 ± 0.02) and RM (0.75 ± 0.03). In all birds neither plumage damages nor FPD were found. In conclusion, the three breeds showed the typical reactivity of rural breeds adapted to alternative and organic rearing systems; the anti-predatory response, the plasma corticosterone concentration and the H/L ratio could be considered a positive adaptation indicator.